Daratumumab for the Treatment of Multiple Myeloma - Torben Plesner; Jakub Krejcik (Frontiers in Immunology, 2018)
This mini-review will summarize the present state of development of the CD38 antibody daratumumab for the treatment of multiple myeloma.